The Heidelberg Catechism: a hidden creedal text and catechetical manual in the Malawian Reformed Church 1889-2012 - Zeze, W. S. D. (Acta Theologica, 2014)
This article focuses on the reception and the status of the Heidelberg Catechism in the Church of the Central Africa Presbyterian (CCAP) Nkhoma Synod in Malawi between 1889 and 2012. The constitution, the church order and the liturgical formularies of the CCAP Nkhoma Synod equally mention that the Heidelberg Catechism is one of the church’s doctrinal standards. The Catechism had never been translated into the official language of this Church, implying that the content of the catechism has been withheld from its members. This leads to the following questions: Was the Heidelberg Catechism really received in the Nkhoma Synod? Why did the Nkhoma fail to make the content of the catechism available to its members? Did this Church realize the implication of a failure to translate the catechism into its official language? Therefore, this article argues that the Catechism had very little or no influence on the Church’s theological discourse and practice.